Honorific Sunda Language in Buru Island - Azwan, Azwan; Bugis, Riki; Kaharuddin, Kaharuddin; Hajar, Ibnu; Sumiaty, Sumiaty; Susiati, Susiati (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study tries to describe the honorific usage in Sunda language on Buru Island as it relates to gender. This study is qualitative in nature. A modest level of participant observation, recording, and recording procedures were used to gather the data. The study's findings revealed that among other things, (1) honorifics on the male sex include honorifics for brothers in the form pamegut, honorifics for other brothers in the form aa', and honorifics for younger brothers in the form ujang; honorifics for husbands in the form caroge, bapak, and ayah; honorifics for fathers in law in the form mitoha and bapak; honorifics for young adults in the form jaja (2) Honorifics on the fa male sex include garwa, mama, and ibu for the wife, nyai for girls, teteh and neng for sisters and younger sisters, mitoha, mama, and ibu for the mather in law, bibi for the aunt, ema for the mother, nini for the grandmother, and unyut for the parents of the grandma.